Effect of Instability Training Equipment on Lower Limb Kinematics and Muscle Activity - Pfusterschmied, J.; Lindinger, S.; Buchecker, M.; Stöggl, T.; Wagner, H.; Müller, E. (Sportverletzung · Sportschaden, 2013)
To improve the effectiveness of training or therapy, it is important to know the benefits for each type of instability training equipment. The aim of this study was to show differences in lower limb kinematics and muscle activation during single leg standing on a slackline (SL) compared to a multi-functional rocker board (MD) and an air cushion (AC). In 14 subjects, mean angular velocity of the hip, knee and ankle, as well as the muscle activity (iEMG) from six lower limb muscles were recorded during 12 s of single leg standing task. Ankle in-/eversion and knee ab-/adduction angular velocity were highest for SL followed by MD and AC (all p < 0.05), as well as in the hip flex-/extension angular velocity with higher values for SL compared with AC (p < 0.01). Regarding iEMG, the rectus femoris muscle showed higher values for SL compared with MD (p < 0.05) and AC (p < 0.01). iEMG of biceps femoris muscle demonstrated higher values for MD compared to AC (p < 0.05), but with no difference to SL. Balancing on a SL is a more challenging exercise for the postural control system compared to MD and AC, and affects the knee and hip joint motion in particular.
Keywords: slackline; postural control; proprioception; injury prevention